Postoperative Capecitabine with Concurrent Intensity-Modulated Radiotherapy or Three-Dimensional Conformal Radiotherapy for Patients with Stage II and III Rectal Cancer. - Ning-Ning Lu; Jing Jin; Shu-Lian Wang; Wei-Hu Wang; Yong-Wen Song; Yue-Ping Liu; Hua Ren; Hui Fang; Xin-Fan Liu; Zi-Hao Yu; Ye-Xiong Li (PLoS ONE, 2015)
The aim of this study was to evaluate the survival outcomes and toxicity of postoperative chemoradiotherapy with capecitabine and concurrent intensity-modulated radiotherapy (IMRT) or three-dimensional conformal radiotherapy (3D-CRT) in patients with stage II and III rectal cancer.We recruited 184 patients with pathologically proven, stage II or III rectal cancer. Following total mesorectal excision (TME), the patients were treated with capecitabine and concurrent IMRT/3D-CRT. The treatment regimen consisted of two cycles of oral capecitabine (1600 mg/m2/day), administered twice daily from day 1-14 of radiotherapy, followed by a 7-day rest. The median pelvic dose was 50 Gy in 25 fractions. Oxaliplatin-based adjuvant chemotherapy was administered after the chemoradiotherapy.The 5-year overall survival, disease-free survival and locoregional control (LRC) rates were 85.1%, 80% and 95.4%, respectively. Grade 3 and 4 toxicities were observed in 28.3% of patients during treatment. Grade 3 or 4 late toxicity, including neurotoxicity or gastrointestinal toxicity, was only observed in nine patients (4.9%).This study demonstrated that capecitabine chemotherapy with concurrent IMRT/3D-CRT following TME is safe, is well tolerated and achieves superior LRC and favorable survival rates, with acceptable toxicity.